Anomalous heat flow in 8-Pmmn borophene with tilted Dirac cones. (5th October 2018) - Sengupta, Parijat; Tan, Yaohua; Bellotti, Enrico; Shi, Junxia
Abstract: We analytically establish an anomalous transverse flow of heat in 8- Pmmn borophene, one of the several two-dimensional allotropes of Boron. The dispersion of this allotrope contains a pair of anisotropic and tilted Dirac cones which are gapped by placing the 2D B sheet under an intense circularly-polarized illumination. A gap in the Dirac dispersion leads to a finite Berry curvature and connected anomalous Hall effects. In the case of thermoelectrics, this manifests as a heat current perpendicular to the temperature gradient—the thermal Hall effect. A quantitative calculation of the attendant thermal Hall conductivity reveals dependence on the intrinsic anisotropy and tilt of the Dirac cone. Further, by estimating the longitudinal thermal conductivity using the Wiedemann–Franz law, we also outline steps to compute the thermal Hall angle that gauges the generation efficiency of such transverse heat processes. Finally, we touch upon the idea of thermal rectification wherein the direction of flow of the anomalous heat reverses through a simple switch of the polarization of incident light and is of interest in thermal logic circuits.